Real appreciation as an automatic channel for redistribution of increased government non-tax revenue - Erling Holmøy (Statistics Norway, Research Department, 2006)
The paper analyses how equilibrium adjustments of the wage rate affect the scope for tax rate reductions when the government experiences an exogenous increase in non-tax revenues. It shows within a stylized model that increased revenue in the form of a tradable will increase the wage rate, which diminishes the scope for tax rate reduction, provided that the initial wage dependent government net expenditures are positive. In this case the wage rate adjustment represents an automatic channel for redistributing increased non-tax government revenues. When the revenue increases in the form a non-tradable, the wage rate adjustment reinforces the scope for tax rate reduction. Simulations on a CGE model of the Norwegian economy confirm the theoretical results, and demonstrate that the fiscal wage effect can be strikingly large.
Keywords: D58; H22; H61; 330; Tax incidence; fiscal policy; general equilibrium effects